Optimising posture: an experimental study of posture support for comfort among Universiti students - Alias, Ayuni Nabilah; Karuppiah, Karmegam; Sanmugam, Kaushaalya (Human Resources Management Academic Research Society (HRMARS), 2024)
Introduction: Long periods of sitting contribute to musculoskeletal disorders (MSD), which can lead to occupational injuries. Introducing posture support is one of the strategies targeted at alleviating discomfort caused by prolonged sitting. The purpose of this study is to determine the effectiveness of posture support in improving muscle comfort during prolonged sitting among university students. Methods: An experimental study was conducted with 32 participants, evenly divided into control and experimental groups of 16 each. The experimental group received posture support during the two-hour simulation, but the control group did not. The Short-Form McGill Pain Questionnaire and Visual Analogue Scale were used to assess the subjects' level of discomfort every 15 minutes. Results: The control group's mean discomfort ratings for several body areas, including the neck, shoulders, arms and hands, upper back, lower back, buttocks, thighs, knees, feet, and ankles, were substantially higher than the experimental group's (p<0.05). Conclusion: Posture support effectively alleviates discomfort in students' sitting posture, as indicated by the experimental group's reduced discomfort. To better understand this phenomenon, future research should include larger sample sizes, longer study periods, and real settings in university’s lecture hall.